3D printing of liquid crystal elastomers-based actuator for an inchworm-inspired crawling soft robot - Song, Xiaowen; Zhang, Weitian; Liu, Haoran; Zhao, Limeng; Chen, Qi; Tian, Hongmiao (Frontiers in Robotics and AI, 2022)
Liquid crystal elastomers (LCEs) have shown great potential as soft actuating materials in soft robots, with large actuation strain and fast response speed. However, to achieve the unique features of actuation, the liquid crystal mesogens should be well aligned and permanently fixed by polymer networks, limiting their practical applications. The recent progress in the 3D printing technologies of LCEs overcame the shortcomings in conventional processing techniques. In this study, the relationship between the 3D printing parameters and the actuation performance of LCEs is studied in detail. Furthermore, a type of inchworm-inspired crawling soft robot based on a liquid crystal elastomeric actuator is demonstrated, coupled with tilted fish-scale-like microstructures with anisotropic friction as the foot for moving forwards. In addition, the anisotropic friction of inclined scales with different angles is measured to demonstrate the performance of anisotropic friction. Lastly, the kinematic performance of the inchworm-inspired robot is tested on different surfaces.